Pregnancy outcome in isolated oligohydramnios diagnosed in third trimester - Singh, Pratibha; Pipal, Vibha Rani; Pipal, Dharmendra Kumar; Ghuman, Navdeep Kaur; Yadav, Garima; Gothwal, Meenakshi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: The aim of this study was to compare the outcomes of pregnancies complicated by isolated oligohydramnios with the low risk pregnancies with normal amniotic fluid volume. Methods: The present study is a retrospective cohort study of singleton pregnancies diagnosed with Isolated oligohydramnios (AFI≤5) in their third trimester (N=35). Pregnancy outcome was compared with a matched control group of low risk pregnancies with amniotic fluid volume >5 (N=30). Results: The overall incidence of Isolated oligohydramnios was 0.7-0.8%. In oligohydramnios group, significant association were found in null-parity (60% vs 23.33%, p-value<0.005), Fetal growth retardation (25.71% vs 0% p-value<0.02), preterm delivery (22.85% vs 3.33%, p-value 0.025), rate of Induction of labor (40% vs 10%) and cesarean rate for non-reassuring fetal heart rate (20% vs 3.33%, p-value<0.001). Likewise, the incidence of low birth weight was (54.28% vs 13.33%, p-value<0.001) and NICU admissions was (20% vs 0%, p-value<0.01), but there was no difference in Apgar score finding. NICU stay was of short duration and all babies discharged in stable condition, there were no stillbirth or early neonatal death in both groups. Conclusions: Isolated oligohydramnios has an adverse influence on pregnancy and neonatal outcome in the form of FGR, preterm delivery, increased rate of Induction and cesarean section. Despite the high incidence of low birth weight and NICU admissions, the overall early neonatal outcome was similar to the other low risk pregnancies.